PENYULUHAN TENTANG KELUARGA BERENCANA (KB) DI DESA PAKONG PADA WANITA USIA SUBUR TAHUN 2022 - Emi Yunita; Imroatus Soleha (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2023)
The background for holding this family planning program outreach is the fact that there are still many people who do not fully know what family planning is and the types of contraceptives. The purpose of this activity is to increase participants' knowledge and interest in the concept of family planning (KB) programs and types of contraceptives. The material presented is the definition of family planning, purpose, benefits and types of contraceptives. The results obtained after the implementation of this activity were that the participants' knowledge and understanding of the family planning (KB) program increased. Therefore, with this family planning program education as an effort to increase public knowledge and awareness about the importance of making family planning (KB) programs successful. Keywords: Education, women of childbearing age, contraception